Examining Mortality Patterns in the Epidemic Emergence of Poliomyelitis in Southern Ontario, Canada (1900-1937) - Battles, Heather T. (My University, 2013)
This thesis examines patterns in poliomyelitis mortality in Wentworth and York Counties of southern Ontario, Canada, from 1900 to 1937. This period marked polio’s shift from endemic to epidemic status. It was also a time of shifting social, cultural, demographic, and economic patterns. Contemporaries struggled to understand polio’s epidemiology, and even today, with the poliovirus on the verge of global eradication, models to explain its changing patterns and impact continue to be revised.
This thesis uses both qualitative and quantitative data collected from a variety of archival sources, including death, birth, and marriage registrations, census records, and newspaper articles, among other records. This information was used to build a geodatabase which forms the basis for analyses of mortality patterns in relation to age and sex, illness duration, seasonality, nativity, birthplace, ethnicity, and religion. Further analyses included family size, birth order, socioeconomic status, and place of residence patterns.
Examined in the context of Wentworth and York Counties in the early 20th century, the results both reveal a local pattern to polio’s epidemic emergence and provide a means to test broader hypotheses regarding polio’s epidemiological patterns. Specifically, results from this study were compared to the expectations of the intensive-exposure and cross-sex transmission hypotheses proposed by Nielsen and colleagues. Among the most important contributions of this thesis are the results showing a pattern of change over the study period, with two distinct stages. Stage One (1910 to 1927) is characterized by an equal sex ratio and a median known family size of four. Stage Two (1928 to 1937) is characterized by excess male deaths and a median known family size of two. These results link polio mortality patterns to demographic and ecological shifts in the early 20th century and confirm that there is still much to learn from the history of this disease.
Keywords: infectious disease; epidemics; hygiene hypothesis; public health; Toronto; Hamilton; Biological and Physical Anthropology; Biological and Physical Anthropology